Near‐Unity and Narrowband Thermal Emissivity in Balanced Dielectric Metasurfaces. Issue 4 (10th December 2019) - Howes, Austin; Nolen, Joshua R.; Caldwell, Joshua D.; Valentine, Jason
Abstract: Nanostructured materials have provided new freedoms for tailoring thermal emissivity in an ultracompact footprint. However, while many designs have demonstrated large absorption amplitude, this often comes at the expense of angular dispersion or the need for a reflective backplane. Furthermore, metal‐based designs generally have broad linewidths due to large nonradiative damping. Here, a unique approach is outlined for obtaining narrowband near‐unity thermal emissivity through spectrally overlapping two orthogonal lossy Mie‐type modes in dielectric metasurfaces operating in the long‐wave infrared. Operating near the transverse optic phonon frequency of a polar dielectric provides a suitably lossy environment, but also one featuring extremely large permittivity, enabling deeply subwavelength resonator sizes, insensitivity to the angle of incidence, and large quality factors even while operating in the long‐wave infrared. Balancing the oscillator strengths and optical losses of the two overlapped resonances maximizes the absorption, resulting in a 3C‐SiC metasurface with 78% absorptance and a quality factor of 170. This balanced metasurface possesses a quality factor on par with some of the narrowest band thermal emitters in the long‐wave infrared, while possessing a simple architecture and prospects for unity emissivity. Abstract : The role of overlapped Mie‐type modes in dielectric resonators with large permittivity and spectral dispersion is investigated for achieving narrowband thermal emissivity. Balancing the oscillator strengths of the resonant modes and optical losses maximizes the absorption. 3C‐SiC metasurfaces are developed that possess 78% absorptance, quality factor of 170, and are insensitive to the incident angle.